Reformulation of Sale And Purchase Agreement Regulations in Creating Legal Certainty and Justice in The Transfer of Land Rights in Indonesia - Fathoni, M. Yazid; Sulistiyono , Adi; Karjoko, Lego (Jurnal IUS Kajian Hukum dan Keadilan, 2024)
Even though Indonesia has promulgated Act Number 5 of 1960 concerning Basic Agrarian Principles Regulations, this regulation cannot provide legal certainty and justice for the parties in the sale and purchase of land rights agreements. When judges decide cases involving property rights sale and purchase agreements, they base their decisions on legal procedures and sources, which demonstrate this uncertainty and injustice. The legal sources as references are varied, sometimes BW (Burgerlijk Wetboek, Adat Law (Customary Law), or Act Number 5 of 1960 with Government Regulatiion Number 24 of 1997. This article uses a normative legal research method. In analysis, to create a land rights sale and purchase agreement that can provide legal certainty and justice, the issue needs to be regulated, especially regarding the issue of the various legal sources, and the responsibility of the state in providing legal certainty. For sales and purchase agreements to provide legal certainty and justice, the state must move from a negative publication system to a positive publication system to realize the constitutional rights of Indonesian citizens in Article 28 D UUD 1945.